2013
DOI: 10.1016/j.jmbbm.2013.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The impact of discrete compartments of a multi-compartment collagen–GAG scaffold on overall construct biophysical properties

Abstract: Orthopedic interfaces such as the tendon-bone junction (TBJ) present unique challenges for biomaterials development. Here we describe a multi-compartment collagen–GAG scaffold fabricated via lyophilization that contains discrete mineralized (CGCaP) and non-mineralized (CG) regions joined by a continuous interface. Modifying CGCaP preparation approaches, we demonstrated scaffold variants of increasing mineral content (40 vs. 80 wt% CaP). We report the impact of fabrication parameters on microstructure, composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 46 publications
1
54
0
Order By: Relevance
“…The suspensions were maintained at this temperature for 2 h to completely freeze the suspension followed by sublimation of the ice crystals at 0°C and 200 mTorr to produce dry scaffolds with pores > 150 mm. 18,23 Scaffold crosslinking and hydration CG scaffolds were dehydrothermally crosslinked at 105°C for 24 h under vacuum (<25 torr) in a vacuum oven (Welch, Niles, IL) following lyophilization. Scaffolds were sterilized in ethanol and rinsed several times in phosphatebuffered saline (PBS) before use.…”
Section: Precursor Suspension Preparationmentioning
confidence: 99%
“…The suspensions were maintained at this temperature for 2 h to completely freeze the suspension followed by sublimation of the ice crystals at 0°C and 200 mTorr to produce dry scaffolds with pores > 150 mm. 18,23 Scaffold crosslinking and hydration CG scaffolds were dehydrothermally crosslinked at 105°C for 24 h under vacuum (<25 torr) in a vacuum oven (Welch, Niles, IL) following lyophilization. Scaffolds were sterilized in ethanol and rinsed several times in phosphatebuffered saline (PBS) before use.…”
Section: Precursor Suspension Preparationmentioning
confidence: 99%
“…These efforts have included optimization of scaffold pore structure (porosity and pore anisotropy), 32, 33 soluble factor cocktails to balance proliferation and phenotypic stability, 34, 35 glycosaminoglycan (GAG) content to mediate transient sequestration of growth factors, and structural reinforcement via the incorporation of CG membranes structures. 36 Recently we described a calcium phosphate mineralized CG (CGCaP) scaffold with potential application for bone tissue engineering and as a component of an osteotendinous repair biomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Also mineralization of hMSCs in the Col-GAG scaffolds occurred at the periphery whereas MC-GAG scaffolds showed good consistent mineralization throughout the scaffold. The scaffolds were relatively similar in porosity, but previous studies showed that these scaffolds differ in terms of presence of nanoparticulate calcium phosphate particles and elastic moduli which may help explain differences in mineralization [47][48] .…”
Section: Growth-factor Independent Osteogenic Induction Of Hmscsmentioning
confidence: 96%